Influence of various factors on the steel oxidizing process during heating in open-flame furnaces - S. M. Kozlov; V. I. Timoshpolsky; I. A. Trusova; V. V. Filippov; P. E. Ratnikov (Литьë и металлургия)
The regularities of forming scale on the surface of metal during heating in high-temperature open-flame furnaces are given. Application of the magistral asymptotic optimization method for optimal thermal technologies designing in respect of scaling is grounded.